High Responsivity Visible Blind Pd/Al2O3/MoS2/ITO MISM UV Photodetector - Singh R.; Srivastava A.; Jit S.; Tripathi S. (My University, 2025)
In the present letter, Pd/Al2O3/MoS2/ITO MISM UV photodetector structure is proposed and analyzed. For the proposed photodetector, responsivity is 488 A/W, detectivity is 8.22× 1012 Jones and external quantum efficiency (EQE) is 1.9× 105%, at wavelength 308nm, 1V bias and light intensity 13.6μW/cm2. Thus, proposed MISM photodetector device gives significant performance improvement over other UV photodetectors. © 1989-2012 IEEE.